Interpretasi Jurnalis Perempuan Kota Palembang Terhadap Feminisme Di Film Bombshell - Tri Andini Firanti; Sumaina Duku; Ahmad Harun Yahya (Social Science and Contemporary Issues Journal, 2024)
ABSTRACT: This researcher discusses the issue of feminism in a film entitled Bombshell. The title of this research is a female journalist's interpretation of feminism in the film Bomshell. Where this research aims in the long term is to provide input to film producers or directors regarding the audience's acceptance of female journalists in the city of Palemang regarding the issue of feminism in the film Bombshell. In this research, the researcher used a qualitative method with an Encoding and Decoding reception analysis approach, using Stuart Hall's reception theory. This is to observe the results of the collation between audience discourse and media discourse. Understanding the existence of the issue of feminism is a matter of differences in interpretation between informants using observation techniques, interviews, and documentation of the results obtained from this research, namely that the five informants gave different meanings to the issue of feminism in the film Bombshell, based on the results, knowledge, patterns different thoughts and experiences. Thus, the results obtained from this research were four informants who agreed with the message, issues and all segments conveyed by the film Bomshell, which means being in a position of Dominant Hegemony, and there was one informant who disagreed and gave his own views on one of the segments in the film. the bombshell. which means being in a negotiation position. The conclusion of this research is that it will hopefully provide information, insight and hopefully the audience will be able to take away the moral values and messages contained in the film. With this research, it is hoped that viewers will have active skills in interpreting the messages contained in film media.